2014
DOI: 10.1016/j.agee.2014.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Tillage and nitrogen fertilization effects on nitrous oxide yield-scaled emissions in a rainfed Mediterranean area

Abstract: There is a strong need to identify the combination of tillage and N fertilization practices that reduce the amount of nitrous oxide (N 2 O) emissions while maintaining crop productivity in dryland Mediterranean areas. We measured the fluxes of N 2 O in two field experiments with 3 and 15 years since their establishment. In the long-term experiment, two types of tillage (NT, notillage, and CT, conventional intensive tillage) and three mineral N fertilization rates (0, 60 and 120 kg N ha Our results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 53 publications
7
46
3
Order By: Relevance
“…That increase could offset the amount of C sequestered under reduced tillage and no-tillage, since N 2 O has a global warming potential 298 times greater than CO 2 (Six et al 2004). However, recent works have found lower N 2 O emissions when no-tillage is practiced in the long term due to a reduction of anaerobic microsites in the soil (Plaza-Bonilla et al 2014;van Kessel et al 2013). These last aspects indicate that future research must take into account the whole C footprint associated to the long-term effects of agricultural practices on greenhouse gas emissions in dryland soils, taking advantage of long-term field experiments and properly validated models.…”
Section: Adoption Of More Efficient Water Management Practicesmentioning
confidence: 99%
“…That increase could offset the amount of C sequestered under reduced tillage and no-tillage, since N 2 O has a global warming potential 298 times greater than CO 2 (Six et al 2004). However, recent works have found lower N 2 O emissions when no-tillage is practiced in the long term due to a reduction of anaerobic microsites in the soil (Plaza-Bonilla et al 2014;van Kessel et al 2013). These last aspects indicate that future research must take into account the whole C footprint associated to the long-term effects of agricultural practices on greenhouse gas emissions in dryland soils, taking advantage of long-term field experiments and properly validated models.…”
Section: Adoption Of More Efficient Water Management Practicesmentioning
confidence: 99%
“…The model has been widely tested in upland soils (Plaza-Bonilla et al, 2014;Scheer et al, 2014;Congreves et al, 2015;Migliorati et al, 2015;Weiler et al, 2017). The model includes submodels for plant yield, crop residues and organic matter, soil water and temperature dynamics, and C and N gas fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to, we found a significant interaction between tillage and campaign (rainfall) in wheat yields: NT tended to increase the grain yields in the dry campaign while the opposite tendency was observed in the normal campaign 12/13. These findings were in agreement with the tendency reported in the literature, CT overall enhances greater crop yield in experiments with high water and nutrient availability (Chatskikh and Olesen, 2007), whereas in semiarid conditions, longterm NT may result in higher yield due to the decrease in water evaporations and the enhancement in water availability and soil fertility (De vita et al, 2007;Morell et al, 2011;Plaza-Bonilla et al, 2014a). Those results observed in all campaigns were in agreement with Van Kessel et al (2013) and Pittelkow et al (2015), no significant differences in crop yield were found between NT/MT and CT systems under rainfed conditions similar to those of our experiment (long-term tillage systems (> 10 years), dry climate, crop rotation with retention of crop residue and low N input).…”
Section: Crop Yield and Yield-scaled N 2 O Emissions In Conservation supporting
confidence: 83%
“…This fact highlights the importance of carrying out long-term field experiment in order to assess the effects of changes in physical, chemical and biological soil properties after several years of NT or MT on N 2 O emissions. In Mediterranean areas, little effect has been described overall between tillage systems (Plaza-Bonilla et al, 2014a;Guardia et al, 2016a). Other concern associated to conservation tillage (NT/MT) compared to CT is the decline in crop yield, often described across different climates zones in the literature review.…”
Section: ) Diversification Of Crop Species Grown In Sequences And/ormentioning
confidence: 99%
See 1 more Smart Citation